The European Nucleotide Archive in 2022. Issue Volume 51:Issue D1(2023) (18th November 2022) - Burgin, Josephine; Ahamed, Alisha; Cummins, Carla; Devraj, Rajkumar; Gueye, Khadim; Gupta, Dipayan; Gupta, Vikas; Haseeb, Muhammad; Ihsan, Maira; Ivanov, Eugene; Jayathilaka, Suran; Balavenkataraman Kadhirvelu, Vishnukumar; et al.
Abstract: The European Nucleotide Archive (ENA; https://www.ebi.ac.uk/ena ), maintained by the European Molecular Biology Laboratory's European Bioinformatics Institute (EMBL-EBI), offers those producing data an open and supported platform for the management, archiving, publication, and dissemination of data; and to the scientific community as a whole, it offers a globally comprehensive data set through a host of data discovery and retrieval tools. Here, we describe recent updates to the ENA's submission and retrieval services as well as focused efforts to improve connectivity, reusability, and interoperability of ENA data and metadata.